An Analysis of the Second Grade Syllabus for Bilingual Elementary School Level - Nanda Miranda; Zulfadli A. Aziz (Universitas Syiah Kuala, 2015)
This study analyzed the syllabus for second grade of the elementary level at private bilingual school in Banda Aceh. It is a qualitative case study which analyzed the syllabus using a coding system. Out of six aspects to be reviewed based on Breen’s (2001) concepts, five aspects were fulfilled by the syllabus. However the syllabus did not cover one important aspect for an ideal syllabus, namely local content. Moreover, the syllabus was developed without a balance of language skills. It failed to describe the methods to be used in the teaching and learning processes and only specified a small number of games. On the other hand, this syllabus had a theme-based syllabus design which favors young language learners learning a foreign language. The syllabus had also a good time table for assessment in order to monitor the progress of students during and at the end of the course. Finally, this syllabus specified the teaching objectives which thus enabled teachers to expand the teaching materials.